Perspektif Kultural Pengelolaan Lingkungan pada Masyarakat Adat Cikondang Kabupaten Bandung Jawa Barat - Billyardi Ramdhan; Tatik Chikmawati; Eko Baroto Waluyo (Jurnal Sumberdaya Hayati, 2015)
Peoples of Traditional Cikondang Village, located in the village of Lamajang, Pangalengan, Bandung City West Java have a very close relation to the environment along with its natural resources. This relation is expressed in the form of procedures and rules on the management and utilization of landscape units as well as the diversity of plants as a form of adaptation to the natural environment. This research was conducted through ethnographic method for photographing people’s lives and ethnobotany to know the biological resources that are important to Cikondang’s people’s daily lives. Descriptive and analytical methods are used through interviews with 87 respondents and 4 key informants. Results of research on landscape units that were identified by the community, indicates that in terms of the character, function, and its management there are 9 units of landscape that is both natural landscape and which has been modified by Cikondang community activities. Each unit of the landscape is characterized by vegetation cover according to the type of value in order for daily life. Meanwhile, cultural factors, economic, and political could be a trigger to the landscape transformation of one type of landscape into other landscapes.